Chloramphenicol-induced translation of cat-86 mRNA requires two cis-acting regulatory regions. - Ambulos, N P (1985)
Sequences essential to the chloramphenicol-inducible expression of cat-86, a chloramphenicol acetyltransferase gene, reside in a 144-base pair (bp) regulatory region that intervenes between the cat-86 coding sequence and its promoter. A key regulatory element within the 144-bp segment consists of a pair of inverted-repeat sequences that immediately precede the cat-86 coding region and span the ribosome-binding site for the gene. Because of the location of the inverted repeats, cat-86 transcripts are predicted to sequester the ribosome-binding site in a stable RNA stem-loop structure which should block translation of cat-86 mRNA. Chloramphenicol induction of gene expression is believed to result from ribosome-mediated destabilization of the RNA stem-loop structure, which frees the cat-86 ribosome-binding site, thereby allowing translation. In this study we demonstrated that deletion of 85 bp from the 5' end of the 144-bp regulatory region abolishes inducible expression of cat-86, although the gene is transcribed. This deletion leaves intact both the inverted repeats and the cat-86 coding sequence, and the deletion mutation is not complementable. Therefore, inducible regulation of cat-86 requires the inverted repeats plus an upstream, cis-acting regulatory region. The cis-acting region is believed to control translation of cat-86 mRNA by its essential participation in chloramphenicol-induced opening of the RNA stem-loop. cat-86 deleted for the 85-bp regulatory region and therefore virtually unexpressed was used to select for mutations that restore expression to the gene. An analysis of one mutant plasmid showed that the cat-86 gene is constitutively expressed and that this results from a duplication of the DNA sequence that spans the ribosome-binding site. The duplication provides cat-86 with two ribosome-binding sites. One of these sites is predicted to be sequestered in an RNA stem-loop, and the other is not involved in RNA secondary structure.